2013
DOI: 10.1186/1471-2393-13-146
|View full text |Cite
|
Sign up to set email alerts
|

Health and nutrition knowledge, attitudes and practices of pregnant women attending and not-attending ANC clinics in Western Kenya: a cross-sectional analysis

Abstract: BackgroundAntenatal care (ANC) is a key strategy to decreasing maternal mortality in low-resource settings. ANC clinics provide resources to improve nutrition and health knowledge and promote preventive health practices. We sought to compare the knowledge, attitude and practices (KAP) among women seeking and not-seeking ANC in rural Kenya.MethodsData from a community-based cross-sectional survey conducted in Western Province, Kenya were used. Nutrition knowledge (NKS), health knowledge (HKS), attitude score (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
8
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 29 publications
9
57
8
4
Order By: Relevance
“…The difference may be accessibility of variety of foods in cities than districts. Majority of the mothers in this study, 204 (63.4%) had a good iron supply during pregnancy, which is similar with the study conducted in Western Kenya (62%) (Perumal et al, 2013). This study revealed that, 111(34.5%) of the pregnant mothers had good nutritional practices, which is similar to the study conducted in the East Wollega (Berg et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The difference may be accessibility of variety of foods in cities than districts. Majority of the mothers in this study, 204 (63.4%) had a good iron supply during pregnancy, which is similar with the study conducted in Western Kenya (62%) (Perumal et al, 2013). This study revealed that, 111(34.5%) of the pregnant mothers had good nutritional practices, which is similar to the study conducted in the East Wollega (Berg et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Participants of this study received education on antenatal care which includes dietary aspect during antenatal class. However, this fi nding is inconsistent with a recent study in Western Kenya which reported that gestational age was negatively associated with health knowledge score suggesting that a delay in seeking antenatal clinic may contribute to less health knowledge as the opportunities to receive advice and education are reduced (Perumal et al 2013).…”
Section: Discussioncontrasting
confidence: 56%
“…In the study the mean months of pregnancy during ANC visit was 3.4 months whereas similar study conducted by Perumal et al shows the mean months of pregnancy during ANC visit was 4.5 months. 9,10 These studies showed that of the total sampled 96 pregnant women interviewed all knew about nutrition and slightly more than one third of the pregnant women knew about nutrition from their family, neighbours and friends. Almost half 47 (48.9%) of the pregnant women answered meat, milk, ghee and eggs as nutritional food and only one-third 31 (32.3%) pregnant women knew right answer about types of nutritional food.…”
Section: Discussionmentioning
confidence: 99%
“…The same study showed slightly more than one third (32.9%) pregnant women had low knowledge on nutrition. 10 The study by Arkkola suggest that proper nutrition during pregnancy is considered important for the wellbeing of both mother and foetus and also it showed that maternal nutrition affects the growth and development of the foetus, and also later health outcomes in the offspring. There is strong association between level of dietary pattern and maternal health outcomes.…”
Section: Discussionmentioning
confidence: 99%